Domestic Violence Against Women During The Covid 19 Pandemic In Gorontalo Province - Dedi Sumanto; Asriadi Zainuddin; Mohammad Ramdan Suyitno; Virahmawaty Mahera (Musamus Law Review, 2022)
The phenomenon of violence against women has recently become a prominent issue. This is not only due to the increasing severity of cases of violence experienced by women, but the intensity is even more worrying. This study focuses on domestic violence during the covid-19 pandemic in Gorontalo Province. The method used in this research is field research with a sociological juridical approach to determine the application of law to society, in this case the enforcement of related laws regarding Law Number 23 of 2004 concerning the Elimination of Domestic Violence.The results of this study are forms of domestic violence in the form of physical violence, namely actions that cause pain, fall ill, or seriously injured. Psychological violence, namely actions that cause fear, loss of self-confidence, loss of ability to act, sense of helplessness, and/or severe psychological suffering on a person. Factors causing Domestic Violence (KDRT) which are often found in handling victims, include: Perpetrators who cheat or have WIL, Communication factors that are not harmonious, There are influence factors from the family either from the victim or perpetrator, Socio-economic factors, Perpetrators who commit physical violence and sexual violence, perpetrators who do not provide a living or neglect for a long time and from the juridical side the problem of domestic violence (KDRT) is pursued through private law (civil) with divorce. However, the dilemma faced by the victim is that she is not ready to live her own life (as a widow) by bearing a negative predicate from the community.